The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pcbi.1004297
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Diffusive States of Rho GTPase in Live Cells: Towards In Vivo Biochemistry

Abstract: Resolving distinct biochemical interaction states when analyzing the trajectories of diffusing proteins in live cells on an individual basis remains challenging because of the limited statistics provided by the relatively short trajectories available experimentally. Here, we introduce a novel, machine-learning based classification methodology, which we call perturbation expectation-maximization (pEM), that simultaneously analyzes a population of protein trajectories to uncover the system of diffusive behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 64 publications
(67 reference statements)
2
30
0
Order By: Relevance
“…Importantly, pEMv2 is rooted in physical principles of stochastic processes. Applying non-physical clustering methods to the same data, such as k-means clustering, lead to poor characterization of the underlying diffusive states [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, pEMv2 is rooted in physical principles of stochastic processes. Applying non-physical clustering methods to the same data, such as k-means clustering, lead to poor characterization of the underlying diffusive states [17].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we extend the original pEM framework [17] to now include non-normal modes of diffusion, i.e. we lift the short-time-diffusion approximation.…”
Section: A Maximum Likelihood Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Koo et al recently analyzed the location of the fluorescent reporter, mEos2, when fused to either full-length RhoA, fulllength RhoC, or the HV domain of either RhoA or RhoC. 8 The authors found a similar number of diffusion states for mEos2 when attached to either full-length GTPase or its corresponding HV domain, suggesting the HV domain alone dictates much of the diffusibility of RhoA and RhoC within cells, potentially through its intermolecular interactions. Moreover, the HV domain chimeras of RhoA and RhoC were found to be dissimilar.…”
Section: Introductionmentioning
confidence: 99%